Hubungan antara Pilar Pembangunan Ekonomi dalam Tujuan Pembangunan Berkelanjutan terhadap Pertumbuhan Ekonomi Pendekatan Akuntansi Arus Dana di Indonesia - Agus Tin Bella Soraya; Rida Perwita Sari (Journal of Management and Bussines (JOMB), 2023)
This research aims to examine the relationship between the pillars of economic development and the economic growth of the fund flow accounting approach in Indonesia. This research method uses a quantitative approach with PLS analysis techniques. The results of this research show that clean and affordable energy has an effect on economic growth, infrastructure innovation industry has an effect on economic growth, and reducing inequality has no effect on economic growth. The conclusion is that clean and affordable energy has an influence on increasing economic growth using the fund flow accounting approach in Indonesia. Then industry, innovation and infrastructure influence the increase in economic growth of the fund flow accounting approach in Indonesia and reducing inequality has no effect on the increase in economic growth of the fund flow accounting approach in Indonesia. Keywords : Energy, Infrastructure, Economic Growth, TPB